2022
DOI: 10.3390/jcdd9080263
|View full text |Cite
|
Sign up to set email alerts
|

The Coadministration of Levosimendan and Exenatide Offers a Significant Cardioprotective Effect to Isolated Rat Hearts against Ischemia/Reperfusion Injury

Abstract: (1) Background: The present study aims to investigate the effect of administration of Levosimendan and Exenatide in various concentrations, as well as of the coadministration of those agents in an ischemia–reperfusion injury isolated heart model. (2) Methods: After 30 min of perfusion, the hearts underwent a 30 min period of regional ischemia followed by a 120 min period of reperfusion. All animals were randomly divided into 12 experimental groups of nine animals in each group: (1) Control, (2) Sham, (3) Digox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Ali Kiraz et al have shown the benefit of levosimendan administration in limiting myocardial necrosis, inflammation, and edema following edema [81]. Recently, the coadministration of exenatide with levosimendan provided additional benefits in cardioprotection against MIRI in experimental models [82]. Despite the established role of levosimendan in acute heart failure management, it is poorly studied in human subjects regarding MIRI prevention.…”
Section: Pharmaceutical Treatmentmentioning
confidence: 99%
“…Ali Kiraz et al have shown the benefit of levosimendan administration in limiting myocardial necrosis, inflammation, and edema following edema [81]. Recently, the coadministration of exenatide with levosimendan provided additional benefits in cardioprotection against MIRI in experimental models [82]. Despite the established role of levosimendan in acute heart failure management, it is poorly studied in human subjects regarding MIRI prevention.…”
Section: Pharmaceutical Treatmentmentioning
confidence: 99%
“…They are also crucial in disease modeling, simulating conditions such as ischemia-reperfusion injury, hypertrophy, and heart failure to understand underlying mechanisms and test therapeutic interventions. In academia, these models serve as an essential educational tool for physiology and pharmacology students, providing hands-on experience with cardiac dynamics [ 49 ].…”
Section: Current Uses and Future Perspectives Of Isolated Heart Perfu...mentioning
confidence: 99%